2021
DOI: 10.1097/ncm.0000000000000473
|View full text |Cite
|
Sign up to set email alerts
|

Negotiation Training for Case Managers to Improve Older Adult Acceptance of Services

Abstract: Purpose of Study: Older adults frequently choose not to accept recommended social support services (e.g., caregiver and home therapy). Social workers/case managers (SWs/CMs) are often caught in the conflict encouraging patients to accept services, but facing resistance. As a result, older adults may experience unsafe home scenarios and hospital discharges. This research sought to examine whether business school negotiation and dispute resolution (NDR) training could ease these conflicts and potentially improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The NCM feel resignation and attrition when the EAR refuses care, such as home caregivers or a place in a residence. Campbell et al reported [ 74 ] how older adults often choose not to accept recommended social support services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NCM feel resignation and attrition when the EAR refuses care, such as home caregivers or a place in a residence. Campbell et al reported [ 74 ] how older adults often choose not to accept recommended social support services.…”
Section: Discussionmentioning
confidence: 99%
“…However, as they refer in their speeches, the NCM are resigned to these refusals, basically, because of the recognition of the principle of autonomy. These experiences are reflected in the study of Campbell et al [ 74 ] who state that case managers have the task of organizing support services for older adults, balancing their right to self-determination/autonomy with the maintenance of their security and that of the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One strategy clinicians utilized to respond to conflict was to assume a collaborative approach involving validation of both older adults' and caregivers' experience, while facilitating shared decisionmaking. In addition, recent studies have used negotiation training to help clinicians navigate conflict with older adults when encountering resistance (Campbell et al, 2020(Campbell et al, , 2021; similar approaches could be used with caregivers. Ultimately, managing MCCs is a collaboration between older adults, clinicians, and caregivers that often requires compromise.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Many have financial resources to meet monthly bills, mortgage, and so on, in addition to hiring of a full-time or part-time caregiver or attendant, but do not know where to begin the process. One small study done in 2021 by Campbell et al 6 looked at the importance of case manager negotiation skills when providing services or placement to skeptical seniors. These researchers identified 4 challenges for case managers: (1) skilled placement that patients are against, (2) differing goals between seniors and their families, (3) challenges when the family and the medical team are not on the same page, (4) an ideological conflict based on “patient wishes are taught to be paramount” (despite unsafe), and (5) when goals of treatment are in conflict.…”
mentioning
confidence: 99%